FACTORS ASSOCIATED WITH HYPERTENSION IN RENTANG VILLAGE, DARUL HIKMAH SUB-DISTRICT, JAYA DISTRICT - Zahara, Hafni; Gustiana, Amni; Afridah, Afridah (TRANSPUBLIKA INTERNATIONAL RESEARCH IN EXACT SCIENCES, 2023)
Hypertension is a growing public health concern. This study aimed to identify factors associated with hypertension among residents of Rentang Village, Darul Hikmah District, Aceh Jaya Regency. Employing a cross-sectional design with community participation, the research found a high prevalence of hypertension. Key risk factors included lifestyle factors such as high salt intake, physical inactivity, and overweight, as well as genetic predisposition. Additionally, environmental factors like stress, air pollution, and limited healthcare access may contribute to the hypertension burden. These findings underscore the need for comprehensive interventions to increase public awareness of healthy lifestyles, address genetic risk factors, and improve healthcare accessibility. Collaborative efforts between the government, community, and stakeholders are essential to reduce hypertension's impact on Rentang Village and surrounding areas.